Pupil findings in a consecutive series of 150 patients with generalised autonomic neuropathy. Issue 10 (5th June 2006) - Bremner, F; Smith, S
Abstract : Aim: To detect and characterise the pattern and extent of pupil abnormalities in patients with generalised autonomic failure. Methods: A consecutive series of 150 patients referred for investigation of symptomatic generalised autonomic failure underwent pupil investigations. Infra-red video pupillography was used to measure resting pupil diameters in light and dark, the light reflex response, the miosis associated with an accommodative effort, and responses to topical administration of various pharmacological agents. The results were compared with data recorded under identical conditions from a cohort of 315 age-matched and sex-matched healthy controls. Results: Overall, two thirds of patients had abnormal pupils (66%) with sympathetic deficit occurring twice as often as parasympathetic deficit. However, the prevalence and type of pupil abnormality showed wide variation according to aetiology—for example, almost all patients with amyloidosis had abnormal pupils, two thirds with pure autonomic failure but less than a quarter with multiple system atrophy. In most patients (85%), pupil abnormalities were bilateral and symmetrical, none had a Horner's syndrome in one eye and a tonic pupil in the other. No significant correlation between the type of pupil abnormality and the predominant type of systemic autonomic deficit was seen in most conditions. Conclusions: The pupils are often affected in autonomic neuropathy, although this is not always apparent either to the patient or to their doctors. Considerable care is needed not only to detect these abnormalities but also to interpret correctly the results of pupil tests in this group of patients.